2013
DOI: 10.1371/journal.pone.0071812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leaf Type and Pesticide Exposure on Abundance of Bacterial Taxa in Mosquito Larval Habitats

Abstract: Lentic freshwater systems including those inhabited by aquatic stages of mosquitoes derive most of their carbon inputs from terrestrial organic matter mainly leaf litter. The leaf litter is colonized by microbial communities that provide the resource base for mosquito larvae. While the microbial biomass associated with different leaf species in container aquatic habitats is well documented, the taxonomic composition of these microbes and their response to common environmental stressors is poorly understood. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Further, many species of Firmicutes are macrolactins producer such as Bacillus , that are resistant to macrolactins and elevate in relative abundance by their products (Yuan et al, 2012a). In the previous studies, the abundance of Beta-proteobacteria and Gamma-proteobacteriaalso showed a positive correlation with agricultural chemicals such as glyphosate, atrazine, permethrin and DDT as they were able to degrade these chemicals (Lew et al, 2013; Muturi et al, 2013). Beta- proteobacteria and Gamma- proteobacteria might be responsible for degradation of macrolactins in soil.…”
Section: Discussionmentioning
confidence: 82%
“…Further, many species of Firmicutes are macrolactins producer such as Bacillus , that are resistant to macrolactins and elevate in relative abundance by their products (Yuan et al, 2012a). In the previous studies, the abundance of Beta-proteobacteria and Gamma-proteobacteriaalso showed a positive correlation with agricultural chemicals such as glyphosate, atrazine, permethrin and DDT as they were able to degrade these chemicals (Lew et al, 2013; Muturi et al, 2013). Beta- proteobacteria and Gamma- proteobacteria might be responsible for degradation of macrolactins in soil.…”
Section: Discussionmentioning
confidence: 82%
“…Other experiments show that male and female 4th instar larvae are competent to pupate at 24-36 hours after they molt from the 3rd instar [70–73], but that high food levels cause them to delay pupation until they attain a maximum weight [53,70,72], and that the time to pupation and the actual size of the adult is affected by the temperature of the larval environment [25,61,70,72,74] as well as food level and density (see above), the type or quality of the food source [6,24,25,7580] and, of course, the sex of the individual [21,37,70–72,74,81].…”
Section: Discussionmentioning
confidence: 99%
“…These provide the nutriment to the microorganism as well as to the Anopheline larvae. Anopheline larvae usually feed on microorganisms (Muturi et al, 2013) and detritus (Merritt et al, 1992). The microorganisms are able to thrive on maize pollen, which in turn serve as Anopheline larvae nutriment.…”
Section: Discussionmentioning
confidence: 99%
“…While the microbial biomass associated with different larva aquatic habitats is well documented, the taxonomic composition of these microbes and their response to common environmental stressors is poorly understood (Muturi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%